CANCER, PREVENTION AND DIAGNOSIS. REPRESENTATIONS OF CANCER FOR PATIENTS AND FAMILIES WHO PARTICIPATE IN THE MUNICIPALITY OF ITAPERUNA RJ - AN EXTENSION- - da Conceição Sampaio Lóss, Juliana; Bastos Boechat, Lais; Venceslau Luz, Letícia; Gonçalves De Castro, Luis Fernando (LINKSCIENCEPLACE, 2026)
The COMVIDA project is presented whose participative methodological praxis is centered on "action research", subsidized by professors and medical students. It is proposed an extensionist practice in favor of better coping of patients in cancer treatment. In the face of so many cancer cases and their different ways of dealing with this disease, the following problem arises: Which representations (perceptions and feelings, meanings of cancer for patients and relatives who attend the institution COMVIDA. It is justified because of the existing demand of patients and family members who attend this institution in the municipality of Itaperuna and who suffer the effects of the disease process and its various spheres. This study aims to critically understand the representations of cancer for patients and family members on cancer treatment, favoring an improvement in the quality of life, facing the cancer, providing improvement in the doctor-patient relationship, through the reception and active listening, based in the person-centered clinical method. This is qualitative field research. These praxis, initiated in 2018, associate weekly attendance, reception, listening to patients extending to relatives - with the practice of medical students, who perform simple anamnesis, which prioritizes biopsychosocial aspects. In this opportunity, clarify important aspects of the disease, as well as the effects of chemotherapy and radiotherapy, as well as the importance of good commitment to treatment, there are motivational lectures that help to cope with the disease, even in extreme cases it is possible to work the mourning. All collected material was transcribed in its entirety and analyzed through Bardin’s content analysis.